2014
DOI: 10.1186/1746-1596-9-113
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP1B1 L432V polymorphism with urinary cancer susceptibility: a meta-analysis

Abstract: BackgroundThe Cytochrome P450 1B1 (CYP1B1) is a key P450 enzyme involved in the metabolism of exogenous and endogenous substrates. Previous studies have reported the existence of CYP1B1 L432V missense polymorphism in prostate, bladder and renal cancers. However, the effects of this polymorphism on the risk of these cancers remain conflicting. Therefore, we performed a meta-analysis to assess the association between L432V polymorphism and the susceptibility of urinary cancers.MethodsWe searched the PubMed datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In non-small cell lung carcinoma, the over-expression of miR-582-3p targets SFRP1 [18]. Studies have also indicated that SFRP1 is a direct target gene of both miR-27a and miR-127-3p [16,19]. In addition, Yang et al discovered that SFRP1 is likely to affect skeletal muscle development and is regulated by miR-1/206 [20].…”
Section: Introductionmentioning
confidence: 99%
“…In non-small cell lung carcinoma, the over-expression of miR-582-3p targets SFRP1 [18]. Studies have also indicated that SFRP1 is a direct target gene of both miR-27a and miR-127-3p [16,19]. In addition, Yang et al discovered that SFRP1 is likely to affect skeletal muscle development and is regulated by miR-1/206 [20].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, no association was found. However, another meta-analysis (1658 cases and 1593 controls) showed that the CYP1B1 L432V polymorphism was associated with urinary cancer risk [210].…”
Section: Urinary Bladder Cancermentioning
confidence: 99%
“…Numerous studies have been conducted to ascertain the association of CYP1B1 polymorphism and susceptibility to cancers such as endometrial and urinary cancer. 26 , 27 But studies regarding its association with oral cancer susceptibility are woefully lacking. To the best of our knowledge, till date no study has been conducted which analyses the CYP1B1 polymorphism and its association with the oxidant -antioxidant status in oral premalignancy and malignancy.…”
Section: Discussionmentioning
confidence: 99%